Development of Self-Regulation Scale for Adolescents - Furkan Kaşıkcı; Selahiddin Öğülmüş (Ankara Üniversitesi Eğitim Bilimleri Fakültesi Dergisi)
This study aims to develop the Self-Regulation Scale for Adolescents. EFA and CFA were conducted to test the scale's construct validity during the development process. In the EFA analysis, the scale has a total of 11 items and a one-dimensional structure; It was concluded that it explained 51% of the variance in self-regulation. As a result of the CFA analysis, it was concluded that the scale had a good fit (χ2 / Sd = 4.55; CFI = .93; TLI = .91; SRMR = .041; RMSEA = .089). To test the item discrimination of the scale, ICC was calculated for each item and it was concluded that the items had good discrimination. The gender measurement invariance of the scale was made and it was concluded that the scale measures the same construct in both men and women. Cronbach Alpha, McDonald Omega Reliability, and Combined Reliability (CR) values were calculated to test the measurement reliability. Cronbach Alpha coefficient was .90; McDonald Omega Confidence (ω) coefficient and CR value was .89 As a result, it was concluded that the Self-Regulation Scale for Adolescents had acceptable and satisfactory psychometric properties in measuring the self-regulation skills of high school students.